(untitled) (SAARC Journal of Agriculture, 2021)
Immunostimulants have been used as a prospective substance against several disease events in aquaculture, although subsequent impact is not clearly explored yet. The present study was conducted to investigate the use of immunostimulants for fish health management in Mymensingh district of Bangladesh. Questionnaire survey was performed with a total of 40 fish farmers and 20 chemical and drug retailers. Altogether, 41 immunostimulants under 7 different categories including glucans and polysaccharides, vitamins, minerals, vitamin-mineral premixes, enzymes, nucleic acids and plant extracts were reported. ACI, Eon, Acme, Square, Renata and SK+F were noticed as the prominent sources among 24 listed companies in this study. The most frequently used immunostimulants were recorded as Megavit-aqua (88.75%), Multivitamin (87.5%), Aqua-boost (87.25%), Eskalina (83.25%) and Eon fish grower (82.5%). Farmers in this study mentioned about improved health condition with lower average disease incidence (29.3%) and reduced mortality (65.35%) in fish after application of immunostimulant. The findings of this study will be useful to perform further research regarding the efficacy and impacts of a wide range of immunostimulants used in aquaculture of Bangladesh. SAARC J. Agric., 19(1): 237-248 (2021)